2015
DOI: 10.3109/10520295.2014.989543
|View full text |Cite
|
Sign up to set email alerts
|

Quirks of dye nomenclature. 4. Fuchsine: four shades of magenta

Abstract: Fuchsine, also called magenta, was the second coal tar dye to be produced after mauveine. Fuchsine is composed of a mixture of up to four triphenylmethane dyes that differ only in the number of substituent methyl groups. Unlike mauveine, fuchsine still is widely used today as a biological stain. We describe the progress of fuchsine from its birth as the second coal tar dye, through a variety of modes of manufacture and industrial application, to its current use. We discuss complexities of nomenclature and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Fuchsin, Magenta, Anilinrot, Rosein [42] . New fuchsin was mentioned for the first time in 1899 [43] . The acid dye (Acid Fuchsin or Acid Magenta) was obtained from fuchsin dyes by treating the starting molecules with fuming sulphuric acid [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Fuchsin, Magenta, Anilinrot, Rosein [42] . New fuchsin was mentioned for the first time in 1899 [43] . The acid dye (Acid Fuchsin or Acid Magenta) was obtained from fuchsin dyes by treating the starting molecules with fuming sulphuric acid [28] .…”
Section: Resultsmentioning
confidence: 99%
“…As well Basic Fuchsin dye belongs to the triarylmethane class dyes 14 . This dye has many applications and uses in textile dyeing, leather dyeing, collagen, muscles, mitochondria, and tuberculosis bacilli 15 . It also possesses Grampositive anesthetic, bactericidal and fungicidal effects 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, it has gained research interests due to its potential applications in photodynamic therapy, bacterial stain, and sporadic reports of its utility in organic electronics. [24,[36][37][38][39][40] Ramesh et al have reported an eco-friendly dye-sensitized device (DSSC) based on NF. [17] The excited state relaxation dynamics and photo-processes in TPM dyes are intrinsically interesting for understanding their role in optical and solar cell applications and have been extensively studied using various time-resolved spectroscopic experiments.…”
Section: Introductionmentioning
confidence: 99%